Genetic Survey of Enteroaggregative E.coli in Diarrheic Children under 5 years in Thi-qar governorate (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed to investigate the prevalence of Enteroaggregative E.coli obtained from children of Thi-qarsuffered from diarrhea through PCR detection of virulence factors (aggR, astA, pic) antibiotic resistance andextended spectrum ?-lactamase (ESBL) production. The investigation included collection 430 stool samplesfrom diarrheic children under five years involved both gender and 40 samples as a control from healthychildren , were consulted in (Bint al- Huda Hospital for Gynecology obstetrics and pediatrics , Al-Mousawihospital and private clinics laboratory ) at a period extended from 10th December 2018 -21th July 2019. Atotal of the isolates were diagnosed by different laboratory and molecular method. PCR diagnosis confirmedthe distribution of genes (aggR and astA) within EAEC were (66% and 53%), respectively. The highestresistance to antibiotics was (100%) to ceftazidime and cefpodoxime , (97% ) to ceftriaxone, followed by(96%) for Ampicillin, Sulfa-Trimethoprim and cefuroxime, respectively, and cefixime, amoxiclav, Cefotaximand Tetracycline (94.8%), (92.3%), (85%) and (78.2%), respectively. While the medium resistance was(55.13%) for each of ciprofloxacin , piperacillin-tazobactam, respectively, and Amikacin (51%). Whilethe lowest resistance was to Gentamicin (30.7%) and Imipenem (26.9%). EAEC isolates were multidrugresistance in average 64/66 (96.97%).